Magnificence of the tsars : Ceremonial men's dress of the Russian Imperial Court, 1721-1917 from the collection of the Moscow Kremlin museums - Amelekhina, Svetlana A.; Levykin, Alexey K.; Blakesley, Rosalind P (South Kensington : V&A Publishing, 2009)
Captures the grandeur of Imperial Russia. This book celebrates the majesty of masculine uniform in Russia at its finest. Starting in the 1730s with lavishly embroidered coats and elaborately patterned silk banyans from the wardrobe of Tsar Peter II, it features the dress and uniforms of Emperors and officials of the Russian court.
boek